The Role of Organizational Culture in the Influence of HRM Practices and Transformational Leadership on Organizational Performance - Andriani Fahira; Agustinus Setyawan (Almana: Jurnal Manajemen dan Bisnis)
This study is motivated by the important role of organizational culture, human resources, and transformational leadership in improving the performance of the shipping logistics industry, especially in the Batam area. The logistics industry faces great challenges in maintaining efficiency and competitiveness, so this study aims to understand how these factors interact and influence company performance. Involving 330 respondents selected through purposive sampling technique, the G-Form questionnaire was distributed through social media and in person. Data analysis was conducted quantitatively using SmartPLS software. The results showed that four hypotheses regarding the direct relationship between variables were accepted, while one hypothesis was rejected. For the indirect relationship, two hypotheses were rejected, and no significant mediation effect was found. In conclusion, organizational culture, human resources, and transformational leadership have different influences on the performance of the shipping logistics industry. Further research is recommended to consider social and environmental factors that may also have a significant impact.